THE SPECIAL COURT FOR SIERRA LEONE: THE MANDATE AND THE CHALLENGES - Alabi, Bolaji; Olomojobi PhD, Yinka; -Haliso PhD, Olajumoke Yacob (Journal of Public Policy and Administration, 2019)
Purpose: The Special Court for Sierra Leone was set up in 2002 as a transitional justice mechanism after the country's ten year civil war. The court concluded its sitting in 2013. The study explored the nexus between expectations of the people and the actual mandate of the court in respect of compensation and also ascertained the appropriateness of the court as a transitional justice mechanism. Methodology: The study adopted multi stage sampling technique in selecting the four towns in Sierra Leone which were studied. The major instrument of data collection was validated questionnaire supplemented by a semi structure interview guide. Findings: The study found that though the court had no mandate to compensate victims, 63% of the respondents expected that the court would give monetary compensation to the victims while 60% felt that the victims should have been compensated. The study concluded that there was a divergence between the expectations of people and the actual mandate of the Special Court though the court was the appropriate mechanism at the time for transitional justice in Sierra Leone. Unique contribution to theory, practice and policy:The study recommended that future criminal tribunals employed as transitional justice mechanisms should be empowered to compensate victims and also such tribunals should be ad hoc and sit in the country of conflict.